2023
DOI: 10.1021/acsnano.3c00839
|View full text |Cite
|
Sign up to set email alerts
|

Biotin–Avidin System-Based Delivery Enhances the Therapeutic Performance of MSC-Derived Exosomes

Abstract: Exosomes (EXs) shed by mesenchymal stem cells (MSCs) are potent therapeutic agents that promote wound healing and regeneration, but when used alone in vivo, their therapeutic potency is diminished by rapid clearance and bioactivity loss. Inspired by the biotin−avidin interaction, we developed a simple yet versatile method for the immobilization of MSC-derived EXs (MSC-EXs) into hydrogels and achieved sustained release for regenerative purposes. First, biotinmodified gelatin methacryloyl (Bio-GelMA) was fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Cytoskeleton staining revealed that RAW 264.7 cells cocultured with SrJM for 2 days exhibited more obvious pseudopodia than those of JM and CaJM, indicating typical M2 activation characteristic (Figure 8B). 70 Furthermore, qRT-PCR was used to comprehensively evaluate macrophage polarizationrelated genes, where RAW 264.7 cells were cocultured with the Janus membranes for 2 days. As shown in Figure 8C, compared with JM and CaJM groups, the SrJM group not only significantly upregulated the gene expression of M2 markers and antiinflammatory cytokines (CD206, IL1ra, IL10, and Arg1), but also upregulated the pro-healing growth factors (TGFβ1, VEGFA, and PDGFBB).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytoskeleton staining revealed that RAW 264.7 cells cocultured with SrJM for 2 days exhibited more obvious pseudopodia than those of JM and CaJM, indicating typical M2 activation characteristic (Figure 8B). 70 Furthermore, qRT-PCR was used to comprehensively evaluate macrophage polarizationrelated genes, where RAW 264.7 cells were cocultured with the Janus membranes for 2 days. As shown in Figure 8C, compared with JM and CaJM groups, the SrJM group not only significantly upregulated the gene expression of M2 markers and antiinflammatory cytokines (CD206, IL1ra, IL10, and Arg1), but also upregulated the pro-healing growth factors (TGFβ1, VEGFA, and PDGFBB).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, M2-polarized macrophages produce various anti-inflammatory and pro-healing factors, which are beneficial for bone regeneration . Accumulative evidence has highlighted that biomaterials with immunomodulatory properties could orchestrate the sequential activation of macrophages to promote the rapid resolution of inflammation and guarantee the predominance of M2-polarized macrophages to launch a successful osseointegration process. …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study employed sonication to encapsulate drug loaded micelles with an EV membrane coating that incorporates a CpG label that binds free transferrin to prolong the circulation time of these EVs and enhance their passage through the blood-brain barrier and targeting to glioblastoma cells through specific recognition by abundant transferrin receptor expression at these sites . Some groups have also employed methods to increase the duration of EV-based drug-delivery at a target site by incorporating EVs into a matrix, as was done by a group that employed streptavidin to capture biotin-labeled and drug-loaded EVs in a biotin-labeled matrix prior to applying this matrix to a tissue injury site . Further studies should be performed to improve drug loading procedures for EVs since current drug loading methods (e.g., electroporation, sonication, extrusion, fusion, etc.)…”
Section: Ev Diagnostic Prognostic and Therapeutic Applicationsmentioning
confidence: 99%
“…PEG modification of extracellular vesicles offers an effective strategy to enhance their stability, prolong circulation time in the body, and reduce immune clearance. Selecting PEG with active functional groups (such as NHS-PEG) enables the formation of stable covalent bonds with amino acid residues on the surface of extracellular vesicles (mainly amino groups of lysine or thiol groups of cysteine) [ 94 ]. Alternatively, PEG with lipophilic anchoring groups (such as DSPE-PEG) can be non-covalently modified onto extracellular vesicles by insertion into the lipid bilayer, with the lipophilic portion embedded within the vesicle's lipid bilayer and the PEG chain extending to the outer surface of the vesicle [ 95 ].…”
Section: Overview Of the Exosomesmentioning
confidence: 99%